C-reactive protein and neutrophil count laboratory test requests from primary care: what is the demand and would substitution by point-of-care technology be viable?. Issue 7 (16th April 2019) - Ordóñez-Mena, José M; Fanshawe, Thomas R; McCartney, David; Shine, Brian; Van den Bruel, Ann; Lasserson, Daniel; Hayward, Gail
Abstract : Aims : C-reactive protein (CRP) and neutrophil count (NC) are important diagnostic indicators of inflammation. Point-of-care (POC) technologies for these markers are available but rarely used in community settings in the UK. To inform the potential for POC tests, it is necessary to understand the demand for testing. We aimed to describe the frequency of CRP and NC test requests from primary care to central laboratory services, describe variability between practices and assess the relationship between the tests. Methods: We described the number of patients with either or both laboratory tests, and the volume of testing per individual and per practice, in a retrospective cohort of all adults in general practices in Oxfordshire, 2014–2016. Results: 372 017 CRP and 776 581 NC tests in 160 883 and 275 093 patients, respectively, were requested from 69 practices. CRP was tested mainly in combination with NC, while the latter was more often tested alone. The median (IQR) of CRP and NC tests/person tested was 1 (1–2) and 2 (1–3), respectively. The median (IQR) tests/practice/week was 36 (22–52) and 72 (50–108), and per 1000 persons registered/practice/week was 4 (3–5) and 8 (7–9), respectively. The median (IQR) CRP and NC concentrations were 2.7 (0.9–7.9) mg/dL and 4.1 (3.1–5.5)×10 9 /L, respectively. Conclusions: The high demand for CRP and NC testing in the community, and the range of results falling within the reportable range for current POC technologies highlight the opportunity for laboratory testing to be supplemented by POC testing in general practice.